The Royal Pulse : reminiscing the significance of riverfront development along Sg. Kedah and Sg. Anak Bukit at Alor Setar (Ampang Jajar to Rumah Merdeka) - Hasan, Mohammed Khairul Fahmie (2018)
Urban identity can be simply defined as an interaction with places, where people describe themselves in tems of belonging to a specific place. For this study, it will revive the significance place and the heritage value of riverfront development along Sg. Kedah and Sg. Anak Bukit (Ampang Jajar to Rumah Merdeka) towards authentic places by enhancing the local physical character. The physical character will emphasized on the function of open spaces, waterfront connectivity and conservation of historical feature. The methodology of this study involves the implementation stages of secondary data from government department and existing data from previous researchers which already published. The primary data has been identified through observation and data recorded method. All collected data are synthesized to identify the potential area to be developed and preserved. Based on the strategy and design ideas inspired from concept of ‘The Royal Pulse’ that has been highlighted the importance and significance place from designing the open spaces to be more functional, waterfront connectivity and conservation of historical feature to make the place be more authentic with own true local identity, in facing the modernism in 2020. Bring back the nostalgic value, which to reminiscing the significance place of Ampang Jajar and its context that will give wonderful experience journey that be memorable. Hopefully, this project can be used as a design strategies and guideline for stakeholders in reminiscing the significance place and revive the urban identity to the place that create a different feeling and memorable experience.